Association between carotid intima-media thickness and adiponectin in participants without diabetes or cardiovascular disease of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil). (29th August 2020) - de Almeida-Pititto, Bianca; Ribeiro-Filho, Fernando Flexa; Santos, Itamar S; Lotufo, Paulo A; Bensenor, Isabela M; Ferreira, Sandra RG
Abstract: Objective: The study assessed the association of adiponectin concentration with carotid intima-media thickness (CIMT) in middle-aged participants of the Brazilian Longitudinal Study of Adult Health (ELSA-Brasil) without diabetes or cardiovascular disease. Design: Cross-sectional analyses. Methods: A sample of 687 individuals (35–54 years old) without diabetes or cardiovascular disease was stratified into two categories according to CIMT (< or ≥ 75th percentile). Traditional risk factors, C-reactive protein and adiponectin values were compared between categories by Student's t -test and frequencies by chi-square test. In linear regression models, associations of CIMT with adiponectin, adjusted for adiposity, blood pressure, C-reactive protein and homeostasis model assessment–insulin resistance were tested. Mean CIMT values were compared across quartiles of adiponectin concentrations using analysis of variance. Results: Three hundred and forty-one individuals (49.6%) were women and 130 (19.0%) had three traditional cardiovascular risk factors. Those with elevated CIMT (21.8%) had greater mean values of body mass index (26.2(3.8) vs . 27.7(4.0)kg/m 2, p  < 0.001), waist circumference (86.9(10.1) vs . 90.1(10.8) cm, p  = 0.001), systolic blood pressure (116.2(13.6) vs .121.2(16.1) mmHg, p  < 0.001), homeostasis model assessment index (1.4(0.9–2.4) vs . 1.8(1.1–2.9), p  = 0.011), C-reactive protein (1.2 (0.6–2.6) vs . 1.4(0.8–3.2) mg/l, p  = 0.054) and adiponectin (9.9 (6.0–14.7) vs . 8.9 (5.3–13.8) µg/ml, p  = 0.002) levels than the counterpart, while plasma glucose and lipids were not different between groups. In the adjusted model, blood pressure (directly) and adiponectin (inversely) persisted associated with high CIMT. Mean CIMT was greater in the first quartile of adiponectin when compared with the other three quartiles ( p  = 0.019). Conclusions: Lower adiponectin levels together with higher blood pressure were independently associated with elevated CIMT. Adiponectin concentration may be an independent marker of early structural damage in individuals at low-to-moderate cardiovascular risk.